2015
DOI: 10.1080/14786419.2015.1084304
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective phenylethanoid glycosides from Cirsium setosum

Abstract: Two new phenylethanoid glycosides, namely β-D-glucopyranoside, 1″-O-(7S)-7-(3-methoxyl-4-hydroxyphenyl)-7-methoxyethyl-3″-α-L-rhamnopyranosyl-4″-[(8E)-7-(3-methoxyl-4-hydroxyphenyl)-8-propenoate] (1) and β-D-glucopyranoside, 1″-O-(7S)-7-(3-methoxyl-4-hydroxyphenyl)-7-methoxyethyl-3″-α-L-rhamnopyranosyl-4″-[(8E)-7-(4-hydroxyphenyl)-8-propenoate] (2), together with six phenylethanoid glycosides were isolated from Cirsium setosum. Their structures were elucidated by their spectroscopic data and references. Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…To clarify the anti-HBV activity of caffeoylquinic acids from the ower buds of L. japonica Thunb., as well as four new caffeoylquinic acids (1)(2)(3)(4), together with ve simple caffeic acids (5)(6)(7)(8)17), and fourteen known caffeoylquinic acids (9)(10)(11)(12)(13)(14)(15)(16)(18)(19)(20)(21)(22)(23) are systematically isolated and identied ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the anti-HBV activity of caffeoylquinic acids from the ower buds of L. japonica Thunb., as well as four new caffeoylquinic acids (1)(2)(3)(4), together with ve simple caffeic acids (5)(6)(7)(8)17), and fourteen known caffeoylquinic acids (9)(10)(11)(12)(13)(14)(15)(16)(18)(19)(20)(21)(22)(23) are systematically isolated and identied ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies show that abundant compounds exist in P. asiatica , such as phenylethanoid glycosides (Miyase et al, ), phenolics (Ravn, Nishibe, Sasahara, & Xuebo, ) and various polysaccharides (Yin et al, ), among which phenylethanoid glycosides are the main components of this herb (Li, Liu, Liu, Tsao, & Liu, ; Li, Liu, Liu, & Wang, ). Phenylethanoid glycosides are widely distributed in the plant kingdom, and have been reported to possess various biological activities including antibacterial, cytotoxic, antioxidant, hepaprotective and immunomodulatory properties (Ma et al, ; Nazemiyeh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylethanoid glycosides are widely distributed in the plant kingdom, and have been reported to possess various biological activities including antibacterial, cytotoxic, antioxidant, hepaprotective and immunomodulatory properties (Ma et al, 2015;Nazemiyeh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cirsium setosum is an edible medicinal plant that is widely distributed around the world. It is an important medicinal component in traditional Chinese medicine for many years, which was supported by considerable clinical evidence (Ma et al 2016a). For instance, C. setosum is widely used to treat many types of diseases, including incomplete uterine contraction and bleeding, infectious hepatitis, digestive tract bleeding, cardiovascular disease, and promote aggregation and adhesion of platelets (Lu et al 2015;Ma et al 2016a).…”
mentioning
confidence: 99%
“…For instance, C. setosum is widely used to treat many types of diseases, including incomplete uterine contraction and bleeding, infectious hepatitis, digestive tract bleeding, cardiovascular disease, and promote aggregation and adhesion of platelets (Lu et al 2015;Ma et al 2016a). Modern phytochemical studies revealed that triterpenes, flavonoids, sterols, polyphenols, and glycosides are its main medicinal ingredients (Luan et al 2016;Ma et al 2016b;Ma, Wen, et al 2016). However, little is known in its biosynthesis mechanism.…”
mentioning
confidence: 99%